Development and Validation of a Measure to Assess Early Adolescents’ Perceptions of Caring Student-Teacher Relationships - Whitehead, Jenna; Schonert-Reichl, Kimberly A.; Oberle, Eva; Boyd, Lara (Frontiers in Education, 2021)
There is accruing evidence documenting the importance of caring student-teacher relationships in fostering students’ social and emotional competence (SEC), well-being, and school success, particularly during early adolescence. However, few studies have investigated dimensions of caring student-teacher relationships from the perspective of early adolescents. This study describes the development and validation of the Caring Student-Teacher Relationship (CSTR) scale. Participants included 222 6th and 7th grade middle school students who completed the CSTR and self-report measures of classroom supportiveness, prosociality, well-being, and school functioning. Students also assessed their teachers’ SEC. Classroom teachers (n = 14) completed self-report measures of mindfulness in teaching and burnout, reported on closeness and conflict in their relationships with students, and rated students’ SECs and academic success. Results from an Exploratory Factory Analysis (EFA) indicated high internal consistency of the CSTR and a two-factor solution: Teacher Support and Attunement and Caring Teacher Qualities. Further analyses revealed that the two factors of the CSTR were related in expected directions to measures of teacher support (e.g., academic and personal) and SEC, and to students’ reports of classroom supportiveness, prosociality, well-being, and school functioning. Positive associations of the two CSTR factors to teacher reports of students’ SEC and academic success were also found. The two factors of the CSTR were positively associated with teachers’ reports of mindfulness in teaching and negatively associated with teachers’ burnout. These findings have implications for understanding the role that students’ perceptions of student-teacher relationships may play in promoting their positive adaptation and success in school.